Responsabilidad sancionadora de personas jurídicas, entes sin personalidad y sus administradores - Rebollo Puig, Manuel (Revista de Derecho, 2019)
This Essay deals with the issue of sanctioning responsibility of legal entities, defendingthe thesis that this does not imply an exception to the application of the personalityprinciples of penalties or guilt. Legal entities will respond when they have actedfraudulently or illegally, which will occur when the actions of their representativeshave been so, since the will of the Legal entities is the will of such representatives.In addition, it also addresses the joint responsibility of legal entities and their managers,analyzing their relationship to the principle of non bis in idem and the conditionsthat might be required for their admission.
Keywords: Sanctioning administrative liability; punitive liabiliy of legal entities; responsibility of the administrators; principle of guilt; personality of penalties; non bis in idem